Rachel Vennya's Directive Speech Actions in Promoting Goods and Their Utilization in Advertising Text Learning - Delvia Derita; Agustina (Indonesia Approach Education, 2023)
This research aims to explain Rachel Vennya`s (RV) directive speech acts in promoting goods and services and their use in learning advertising texts and slogans. This type of research is qualitative research with a descriptive method. The data for this research is the speech of celebrities from the RV program when promoting goods and services. Data source is RV's personal Instagram account taken from posts starting November 2020 to November 2022. Data collection uses media review techniques by downloading recordings of these promotional posts. Data validation was carried out through triangulation techniques, while data processing was carried out using three stages, namely the analysis, discussion and conclusion stages. Three findings were obtained from this research. First, there are four types of directive speech acts of RV in promoting goods and services, namely the speech acts of suggesting, commanding, advising, and pleading. Third, directive speech acts and speech strategies can be used as learning media for making advertising texts and slogans in schools. Finally, the research it can be used as a teaching medium in making advertising text and slogans to assist students in producing advertising text and slogans at school.